2010
DOI: 10.3747/co.v17i5.668
|View full text |Cite
|
Sign up to set email alerts
|

Association of Lipid Metabolism with Ovarian Cancer

Abstract: Defects in lipid metabolism have been found to be linked to several diseases, among which atherosclerosis, hypertension, obesity, and diabetes are the most important. Although cancer is chiefly a genetic disease, dietary lipid intake and metabolism are related to some cancer risks, including the risk for ovarian cancer. Higher intake of dietary lipids, systemic lipid metabolism malfunction, and abnormal serum lipid levels are somehow related to ovarian cancer. Overexpression of some lipid metabolic enzymes are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(33 citation statements)
references
References 53 publications
2
30
0
1
Order By: Relevance
“…In addition, the metabolic proteins transketolase and enolase, which are involved in glycolysis and the pentose phosphate pathway, respectively, were found to be differentially expressed by septin-2 inhibition (Figure 4C), demonstrating that septin-2 is involved in various facets of cellular metabolism within EOC. Pathways related to metabolism and energy production have previously been found to contribute to EOC tumorigenesis, as it has been shown that glycolysis drives chemoresistance in EOC and that high levels of fatty acid synthase (FASN) contribute to tumor cell growth through the promotion of human epidermal growth factor [44, 45]. Therefore, it can be hypothesized that the inhibition of septin-2 would exhibit a therapeutic effect in EOC via suppression of tumor metabolic pathways.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the metabolic proteins transketolase and enolase, which are involved in glycolysis and the pentose phosphate pathway, respectively, were found to be differentially expressed by septin-2 inhibition (Figure 4C), demonstrating that septin-2 is involved in various facets of cellular metabolism within EOC. Pathways related to metabolism and energy production have previously been found to contribute to EOC tumorigenesis, as it has been shown that glycolysis drives chemoresistance in EOC and that high levels of fatty acid synthase (FASN) contribute to tumor cell growth through the promotion of human epidermal growth factor [44, 45]. Therefore, it can be hypothesized that the inhibition of septin-2 would exhibit a therapeutic effect in EOC via suppression of tumor metabolic pathways.…”
Section: Discussionmentioning
confidence: 99%
“…In a meta-analysis, 24 of 28 studies reported a positive association between obesity and ovarian cancer ( 9 ). Overexpression of some lipid metabolic enzymes is also found in ovarian cancer ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…Aberrant cellular metabolism in cancer is now well known and is directly related to tumorigenesis in most of the cancers [ 57 , 58 ]. Multiple signaling pathways and several molecules are involved in the synthesis and degradation of the lipids and also the activities of lipid metabolizing enzymes are regulated by a complex interplay between metabolic, tumor suppressor, and oncogenic signaling [ 59 ]. Though loss of HSulf-1, a putative tumor suppressor gene, was well known to promote tumorigenesis, angiogenesis [ 22 , 23 ], and invasion [ 20 ] in breast [ 18 , 21 ] and ovarian [ 23 , 24 ] cancers, the role of HSulf-1 was never elucidated in altered metabolism of ovarian cancer cells so far.…”
Section: Discussionmentioning
confidence: 99%